Seroprevalence of Brucellosis and its Associated Risk Factors in Sheep and Goat in the Farms and Slaughter House in Mymensingh, Bangladesh (Microbes and Health, 2014)
A cross sectional study was performed to determine the seroprevalence and risk factors of brucellosis in sheep and goat on the farms, Veterinary Teaching Hospital of Bangladesh Agricultural University (BAU), and animal slaughter house of Mymensingh, Bangladesh. Sera were prepared after collecting blood samples from sheep (n=101) and goat (n=113). Risk factors relating to brucellosis were determined considering the variables generated from a questionnaire. These variables included animals age, sex, pregnancy, and husbandry system. The sera were tested by Rose Bengal Plate Test (RBPT) for the detection of Brucella abortus specific antibodies in sheep and goat. The results revealed that 5.94% (n=6/101) sera of sheep, and 6.19% (n=7/113) sera of goat were positive for brucellosis. Higher prevalence of brucellosis was recorded in female sheep (7.54%) and goat (6.49%) as compared to male sheep (4.16%) and goat (5.50%), respectively. The sheep and goat above two years of age showed higher prevalence of brucellosis (8.69% and 6.45%) as compared to other ages. No risk factor was found to be statistically significant (p>0.05). Data of this study suggest that sheep and goat could be the reservoir hosts of brucellosis that might constitute a hurdle in the controlling of bovine and human brucellosis. DOI: http://dx.doi.org/10.3329/mh.v3i1.19778 Microbes and Health, June 2014. 3(1): 25-28